Modified conjunctival flap as a primary procedure for nontraumatic acute corneal perforation - Yi-Chen Sun; Jason P Kam; Tueng T Shen (Tzu Chi Medical Journal)
Objective: Appropriate management of nontraumatic acute corneal perforation is always a challenge even with the many advances in surgical materials and techniques. We reported the outcomes of a case series of acute corneal perforation repair using a newly modified conjunctival flap with amniotic membrane transplant (AMT), fibrin glue, and a bandage soft contact lens (BCL). Materials and Methods: A total of 13 consecutive referral cases with nontraumatic acute corneal perforation at the University of Washington were reviewed. All open globes were repaired by a combined surgery with a modified conjunctival flap, AMT, fibrin glue, and BCL. Visual acuity, a slit lamp examination, and the patient-reported pain level were collected preoperatively and postoperatively. Subsequent corneal surgeries to improve visual function were also reviewed. Results: All ocular surfaces of the 13 eyes were stable at postoperative follow-up. Eleven of the 13 patients had the same or worse visual acuity 1 week postoperatively. Nine of the 13 patients achieved better vision 6 months postoperatively. None of the patients developed perioperative or postoperative complications. Five patients with good visual potential underwent further corneal surgeries, including Boston keratoprosthesis and penetrating keratoplasty. The average referral distance was 217 miles and the median number of follow-up visits within 6 months was 4. Conclusions: The combination of a modified conjunctival flap, AMT, fibrin glue, and a BCL could provide a temporary method to stabilize and secure the integrity of the globe as well as the ocular surface after a nontraumatic acute corneal perforation. This approach allows easy follow-up and preserves the eye for future corneal surgery under optimal conditions.